Shakespeare, Tragedy and Menopause The Anxious Womb - McMahon, Victoria L. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
Shakespeare was not only aware of the socio-cultural fears and anxieties generated by the older woman's body but with the characterization of his tragic ageing females, Shakespeare becomes the first literary giant to explore the physiological and psychosocial condition that we have come to know as 'menopause'. Although 'menopause' was not defined as a medical, physiological or sociocultural event for the early moderns, this book argues that such a medical and cultural transition can, in fact, be identified by sub-textual clues distinguished by various embodied anxieties. It explores several ageing women of the Shakespearean tragedies as they transition through this liminal menopausal period. Theoretically underscored by humoral theory, the analysis is metonymically centered upon the womb as the seat of menopausal anxiety. These menopausal undercurrents, not only permeate the dramatic action of each play, but also emanate outward to reflect the medical, physiological, cultural, social, and religious concerns generated by the ageing woman of the early modern period at large. Born and raised in Warwickshire, Dr. V. L. McMahon holds advanced degrees in Education, English, and Theatre. As an arts educator for over thirty years, McMahon has written, taught, and implemented Drama and English curricula in Canada's public school system. Having lectured in the Faculties of Theatre and English at the University of Winnipeg, Canada, McMahon is also an actor, director, playwright, and dramaturge and holds a PhD from the Shakespeare Institute, University of Birmingham, UK.
Chapter 1: Introduction -- Chapter 2: Menopausal Gertrude and the Petrified Womb -- Chapter 3: Menopausal Tamora and the Vegetable Womb -- Chapter 4: Menopausal Volumnia and the Animal Womb -- Chapter 5: Menopausal Lady Macbeth and the Envious Womb -- Chapter 6: Menopausal Cleopatra and the Cyborg Womb -- Chapter 7: Conclusion.
Keywords: European literature -- Renaissance, 1450-1600.; Medicine and the humanities; Theater -- History; Women -- History; Early Modern and Renaissance Literature; Medical Humanities; Theatre History; Women's History / History of Gender